The edge also matters: human threats in a rare Mediterranean habitat for Cantabrian Capercaillie. Issue 4 (11th January 2017) - GONZÁLEZ, MANUEL ANTONIO; FUERTES, BENITO; BLANCO-FONTAO, BEATRIZ; DE FRUTOS, ÁNGEL
Summary: Nature reserves focused on the protection of an endangered species are often restricted to the core of the species' distribution, leaving peripheral populations unprotected due to a lack of specific knowledge. This study describes the factors that potentially contribute to degradation of habitats of a peripheral population of the endangered Cantabrian Capercaillie Tetrao urogallus cantabricus . Using presence/absence data, we compared forest fragmentation, fire risk, and distance from leks to human infrastructure. Forest fragments in which Cantabrian Capercaillie were detected were significantly larger, closer to the nearest occupied fragments, and had a higher proximity index than fragments in which no presence was detected. Eighteen percent of the area of fragments in which Cantabrian Capercaillie presence was detected were placed in the high risk of fire category. Human infrastructure represents a permanent loss of Mediterranean habitat for the Cantabrian Capercaillie. The study area is highly modified by human activities; a priority conservation measure should be inclusion within the Natura 2000 network.